1989
DOI: 10.1123/ijsb.5.4.457
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Film and Video Techniques for Three-Dimensional DLT Repredictions

Abstract: The precision of the kinematic values depends upon the methods of recording a subject’s motion. With the introduction of video recording techniques, questions have arisen concerning the accuracy of video compared with that of 16-mm film. Accordingly, the purpose of this study was to compare the accuracy of the two techniques for point reprediction using the Direct Linear Transformation method. Range poles, serving as boundaries of a cube with 20 known spatial coordinates, were filmed and videotaped. The 20 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 3 publications
0
3
0
4
Order By: Relevance
“…The mean absolute error in the reconstruction of the calibration tree points was calculated to be less than 0.3 cm. Based on the results of Kennedy, Wright and Smith (1989) and Angulo and Dapena (1992), such an error is very low and suggests high precision of the model used. A second-order digital low-pass Butterworth filter, with a cut-off frequency of 5 -7 Hz, depending on the noise level estimated with residual analysis (Winter, 1990), was used for smoothing the three-dimensional coordinates of each anatomical point.…”
Section: Kinematic Analysismentioning
confidence: 94%
“…The mean absolute error in the reconstruction of the calibration tree points was calculated to be less than 0.3 cm. Based on the results of Kennedy, Wright and Smith (1989) and Angulo and Dapena (1992), such an error is very low and suggests high precision of the model used. A second-order digital low-pass Butterworth filter, with a cut-off frequency of 5 -7 Hz, depending on the noise level estimated with residual analysis (Winter, 1990), was used for smoothing the three-dimensional coordinates of each anatomical point.…”
Section: Kinematic Analysismentioning
confidence: 94%
“…A atividade eletromiográfica dos músculos da perna também sofre influência da velocidade da marcha (CHIU; WANG, 2007;DEN OTTER et al, 2004;NYMARK et al, 2005;WARREN;MAHER;HIGBIE, 2004). Warren et al, (WARREN;MAHER;HIGBIE, 2004) JESUS et al, 2015;KENNEDY;SMITH, 1989). Até o presente momento, nenhum estudo foi conduzido com a finalidade de saber as diferenças entre o erro de reconstrução das câmeras digitais e optoeletrônicas.…”
Section: Sabeunclassified
“…The measurement error is better than that reported in other studies of movement analysis using film and video systems (e.g. Kennedy et al, 1989).…”
Section: Discussionmentioning
confidence: 49%
“…Andriacchi et al (1979) reported measurement error ranging from 0.25%-0.31% using a similar polynomial method with 10-29 calibration points. Kennedy et al (1989) compared DLT reconstructions using video and film systems and reported errors of 0.29% and 0.24% respectively. It is evident that measurement error is significantly reduced using the modified polynomial method presented in this study by increasing the number of calibration points.…”
Section: Discussionmentioning
confidence: 99%